Studi Linguistik tentang Penggunaan Bahasa Inggris pada Penyampaian Informasi Kesehatan di Platform Digital - Mariana Mariana; Rudi Purwana (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The increasing use of digital platforms in the healthcare industry has highlighted the importance of effective communication, especially in English, as it is the primary language for disseminating global health information. This study examines the linguistic aspects of English usage in health information delivery on digital platforms, focusing on clarity, accessibility, and accuracy. The research aims to analyze how linguistic features, such as word choice, sentence structure, and tone, impact the comprehension of health-related content by diverse audiences.The study employs a qualitative approach, analyzing a sample of health-related websites, social media posts, and mobile health applications. Discourse analysis is used to identify patterns and strategies in the presentation of information, particularly how technical medical terms are simplified for laypeople.The findings reveal that while most platforms aim for clarity and inclusivity, inconsistencies in language use and overly technical jargon often hinder comprehension. Additionally, the use of complex sentence structures can create barriers, especially for non-native English speakers.The study concludes that improving linguistic accessibility on digital health platforms can enhance public understanding and engagement with health information, contributing to better health outcomes. Recommendations for creating more user-friendly, linguistically accessible content are also provided.